Co-liquefaction of mixed biomass feedstocks for bio-oil production: A critical review. (February 2022) - Li, Qingyin; Yuan, Xiangzhou; Hu, Xun; Meers, Erik; Ong, Hwai Chyuan; Chen, Wei-Hsin; Duan, Peigao; Zhang, Shicheng; Lee, Ki Bong; Ok, Yong Sik
Abstract: Liquefaction is an attractive technology for converting biomass into bio-oil without the requirement for drying feedstock, and the process can be conducted at relatively low temperatures. In the practical application, the treated biomass feedstocks are composed of a mixture of agricultural waste, forestry waste and some organic solid waste. The utilization of co-liquefaction technology is suitable for biomass as it can fully utilize different types of feedstocks and enhance the liquefaction degree of each feedstock. During the co-liquefaction of these blending biomass feedstocks, the individual biomass species can degrade according to their own reaction network that is governed by the unique structural compositions. Furthermore, the reaction intermediates from the degradation of different biomasses can potentially interact with each other. This will affect the reaction characteristics and alter the chemical constituents and properties of the bio-oil produced. The understanding of interaction for the blending biomasses during the co-liquefaction process is of significance for tuning the chemical species and yield of the resulting bio-oil. Thus, this review work focuses on the co-liquefaction behavior of the various biomass feedstocks including lignocellulose, organic solid waste and algae. The influences of the essential operation parameters including solvent types, catalyst types, reaction temperature and time, and the mixing ratio of different biomasses on co-liquefaction behavior are also evaluated in detail. The choice of the proper reaction parameters is dependent on the structural characteristics of mixed feedstocks. Additionally, the co-liquefaction impact on the composition and formation mechanism of bio-oils are investigated. Highlights: Characteristics in co-liquefaction of mixed biomasses are discussed. Influences of essential variables on co-liquefaction are analyzed. Interaction of the reaction intermediates in co-liquefaction are focused. Co-liquefaction mechanism for mixed biomass is compared and analyzed. Advantages, issues and future directions for co-liquefaction are proposed.